Improving Multi-Level NAND Flash Memory Storage Reliability Using Concatenated BCH-TCM Coding - Li, Shu; Zhang, Tong (IEEE transactions on very large scale integration (VLSI) systems, 2010)
By storing more than one bit in each memory cell, multi-level per cell (MLC) NAND flash memories are dominating global flash memory market due to their appealing storage density advantage. However, continuous technology scaling makes MLC NAND flash memories increasingly subject to worse raw storage reliability. This paper presents a memory fault tolerance design solution geared to MLC NAND flash memories. The basic idea is to concatenate trellis coded modulation (TCM) with an outer BCH code, which can greatly improve the error correction performance compared with the current design practice that uses BCH codes only. The key is that TCM can well leverage the multi-level storage characteristic to reduce the memory bit error rate and hence relieve the burden of outer BCH code, at no cost of extra redundant memory cells. The superior performance of such concatenated BCH-TCM coding systems for MLC NAND flash memories has been well demonstrated through computer simulations. A modified TCM demodulation approach is further proposed to improve the tolerance to static memory cell defects. We also address the associated practical implementation issues in case of using either single-page or multi-page programming strategy, and demonstrate the silicon implementation efficiency through application-specific integrated circuit design at 65 nm node.